Optimization of theophylline sustained release tablet formula with HPMC, CMC Na and xanthan gum as matrix component - Agus Siswanto; Sri Sulihtyowati Soebagyo (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2006)
Theophylline has a relatively short half-life (8,1 jam) with a narrow therapeutic window (10 – 20 μg/mL). Sustained-release formulation can produce more uniform serum concentrations with less fluctuation in peaktrough levels. The physical properties of tablet mass and the release profileof drug from hydrophilic matrices are influenced by properties of matrix components, i.e. HPMC (gelling agent), CMC-Na (did not show initial burst release), and xanthan gum (free flowing).The research was done with simplex lattice design (SLD) by using 3 component, i.e. HPMC (A), CMC-Na (B), and xanthan gum (C). Seven formula were obtained that are F1 (100% A), F2 (100% B), F3 (100% C), F4 (50% A & 50% B), F5 (50% B & 50% C), F6 (50% A & 50% C), dan F7 (33,33% A, 33,33% B, 33,33% C). The Optimization parameters of theophylline sustained-release were flow rate of the tablet mass, the compactibility of the tablet mass, and the release rate of theophylline.Based on SLD model; equations, contour plots, and superimposed of contour plots were obtained, by which the optimum formula was determined.Xanthan gum was the most dominant factor in increasing flowability and compactibility of theophylline tablet mass. HPMC was the most dominant factor in decreasing the dissolution rate of theophylline. The most dominant interaction effect to increase flowability and compactibility was the interaction of HPMC, CMC-Na, and xanthan gum. The most dominant interaction effect to increase correlation coefficient of zero order kinetics was the interaction HPMC and CMC-Na. Based on the superimposed contour plots, tablet formula consisting of HPMC (2,3 %), CMC-Na (18,6 %), and xanthan gum (79,1 %) is the optimum tablet formula.Key words: theophylline, HPMC, CMC-Na, xanthan gum, sustained-release